A photo-degradable supramolecular hydrogel for selective delivery of microRNA into 3D-cultured cells. Issue 10 (21st February 2017) - Zhou, Zhengquan; Yi, Qikun; Xia, Tingting; Yin, Wencui; Kadi, Adnan A.; Li, Jinbo; Zhang, Yan
Abstract : A multi-functional supramolecular hydrogel was developed for long-term 3D cell culture, targeted miRNA delivery and easy collection of encapsulated cells. Abstract : Multi-functional supramolecular hydrogels have emerged as smart biomaterials for diverse biomedical applications. Here we report a multi-functional supramolecular hydrogel formed by the conjugate of the bioactive GRGDS peptide with biaryltetrazole that is the substrate of photo-click reaction. The hydrogel was used as a biocompatible matrix to encapsulate live cells for 3D culture. The presence of the RGD epitope in the hydrogelator enhanced the interaction of the nanofiber with integrin over-expressing cells, which resulted in the selective enhancement in the miRNA delivery into the encapsulated U87 cells. The intramolecular photo-click reaction of the biaryltetrazole moiety in the hydrogelator leads to a sensitive photo-response of the hydrogel, which allowed photo-degradation of the hydrogel for release of the encapsulated live cells for further bio-assay of the intracellular species.